Pengaruh Return On Asset (ROA), Dividend Payout Ratio (DPR) Dan Earning Per Share (EPS) Terhadap Harga Saham Pada Perusahaan Manufaktur Di Bursa Efek Indonesia Th 2010 - 2014 - Mubarok, Dzikki khoirul; , Drs. Agus moqorobin MM (2016)
This study aims to look at the influence of the retrun on assets, the dividend payout ratio and earnings per share to the stock price either partially maupu simultaneously on the company's manufacturing companies listed on the Stock Exchange. Independent variables used in this study is the retrun on assets, the dividend payout ratio and earnings per share. The dependent variable in this study is the stock price. The population used in this study are all manufacturing companies listed in Indonesia Stock Exchange in 2010-2014. where the total population is used as many as 17 companies with the data julah 85. The sampling technique used was purposive sampling technique in which the number of observations obtained in this study is 17 samples. The test used in this study is to test the classical assumption (normality, heteroscedasticity, autocorrelation and multicolinearity) and hypothesis test (t test, F test and test of determination). The test results demonstrate the value of the coefficient of determination R2 is equal to 0152. Thus the magnitude of the influence exerted by the variable retrun on assets, the dividend payout ratio and earnings per share to the stock price is 15.2%. While the remaining 84.8% is influenced by other factors not examined in this study. Based on the partial test results showed that the variables retrun on assets, earnings per share positive and significant impact on stock prices, while the dividend payout ratio variable has no effect on stock prices. Based on test results obtained by the simultaneous conclusion that the variable retrun on assets, the dividend payout ratio and earnings per share effect on stock prices. Keywords: Retrun on assets, Dividend payout ratio, Earning per share and stock price.